Abundance Telescopium telescopium at Mangrove Ecosystem in Daruba Pantai Village, Morotai Island - Iswandi Wahab; Nurafni Nurafni; Aricen Rahamati (Musamus Fisheries and Marine Journal, 2020)
Mangroves are one of the most important plants in coastal areas that act as a provider of nutrients for aquatic biota. Telescopium telescopium is one of the gastropod species which is found in many mangrove ecosystem areas. The research objective was to analyze the abundance of Telescopium telescopium and the composition of the mangrove species in the waters of Daruba Pantai Village. This research was conducted from December 2019 to January 2020. The method used is quadrant transect line and Telescopium telescopium observation is done visually or directly. Telescopium telescopium abundance data were analyzed descriptively. The results of the research on mangrove communities were varied, consisting of 4-5 types of mangroves. At station (1) there are 4 types of mangroves, stations (2) and (3) there are 5 types of mangroves. The abundance of Telescopium telescopium at three stations, the highest was at station (3) 0.262 (ind / m²), Station (1) 0.212 (ind / m²) and the lowest was at station (2) 0.142 (ind / m²). The abundance of Telescopium telescopiun is found at three stations and the highest is at station (3) 0.262 (ind / m²). The composition of mangrove species contained in Telescopium telescopium are Rhizopohora apiculata, Ceriops tagal and Rhizopora mucronata.